Disease incidence for first-generation offspring individuals born from residents of radiation contaminated territories of Ukraine as a result of the Chernobyl accident. The observation period is 18 years from the date of birth - Zh. Yaroshenko; S. Guriev; N. Iskra (Kazimierz Wielki University, 2019)
There was conducted an epidemiological study of the health of the first-generation offspring born by residents of radioactively contaminated territories from 1987 to 1999 years until they reached 18 years. The total cohort was 35893 individuals, among whom male offspring constituted 18138 individuals, while female offspring constituted 17755 individuals. There were created 4 groups to study offspring aged 0-3 years, depending on the time of birth of offspring after an accident with a three-year observation period. During the observation period, for the first time there were detected 21344 individuals (100%) with non-tumour diseases by certain classes of diseases ICD-10, of whom male offspring were 10,696 (49.9%), and female offspring - 10738 (50.09%). The main components in the structure of the initially detected non-tumour disease were respiratory diseases (34.45%), diseases of the endocrine system, eating disorders and metabolic disorders (16.27%), digestive organ diseases (15.58%). Together they make up 66.87%. The incidence of diseases among the FGOs of all study groups, respectively, is the following: respiratory diseases - ID by 103 man-years ± m - 59,59 ± 0,65; 25.06 ± 0.43 by 103; 24.23 ± 0.42. In the structure of diseases of the endocrine system, eating disorders and metabolic disorders (E00.0 - E90.9) total incidence of thyroid diseases (E00.0 - E07.0) - 96,6%. The incidence of respiratory disease in all study groups mainly emerged due to acute respiratory infections of the upper respiratory tract, namely: acute nasopharyngitis, sinusitis, pharyngitis, tonsillitis and other diseases in the group upper respiratory tract - chronic diseases of the tonsils and adenoids, among others acute respiratory infections of the lower respiratory tract - acute bronchitis and bronchiolitis. The pathology of the digestive system of the FGOs of all four study groups emerges through "Gastritis and duodenitis, K29-K29.9", "gallbladder and biliary diseases pathways, K80-K83.9 "and" hernias, K40-K46.9 "," diseases of the mouth, salivary glands and jaws, K00.0-K14.9". Respiratory disease rates are higher among offspring of first and second groups in (born in the period of 01.03.1987-28.02.1993) compared to the third and fourth groups (years of birth 01.03.1993-28.02.1999). The lowest levels are relevant for the fourth group. The highest incidence rates of thyroid disease are relevant for offspring of the first group compared to the other subject groups. At the same time, the incidence rates among the offspring of the second group are evidently higher than of the third and fourth groups. The lowest levels are by the fourth group. The development of thyroid disease during the 18 years of observations of each study group is characterized by the appearance of more complex nosological forms of thyroid pathology starting from 7 - 9 years. The incidence rates of digestive diseases are the highest by the first study group, the lower - by the second, and the lowest - by the fourth. The most vulnerable to the development of morbidity in the above classes of diseases among the FGOs is the life span from 7 to 15 years. This is evidenced by the increased incidence of respiratory diseases with maximum indicator at the age of 13-15 years, of thyroid diseases - at the age of 7-9 years, of digestive organs - at the age of 10-12 years.